PARADIGMA WAHDATUL ‘ULUM UNIVERSITAS ISLAM NEGERI SUMATERA UTARA SEBUAH UPAYA FILOSOFIS MENGHADAPI ERA DISRUPSI - Fridiyanto Fridiyanto (Journal Analytica Islamica, 2019)
Abstract this article argues that Wahdatul ‘Ulum Paradigm of UIN North Sumatera as an effort inmaking a distinctive knowledge paradigm. The research methodology is qualitative with single casestudy design. The findings of research are UIN North Sumatra make a moderate solution with combiningWahdatul ‘Ulum and Trans disciplinary concepts to be integrated. Wahdatul ‘Ulum Paradigm tries tosolve knowledge dichotomy problems and then Trans disciplinary is a transformative approach to solvethe real society problems. Wahdatul ‘Ulum Paradigm is adaptive philosophy in Disruptive Era becausethe Trans disciplinary can be used in engineering knowledge and practical technology.Key Words: Wahdatul ‘Ulum, Transdisipliner, Era Disrupsi, UIN Sumatera Utara